Assessment of Cardiac Masses by Cardiac Magnetic Resonance Imaging: Histological Correlation and Clinical Outcomes. Issue 1 (8th January 2019) - Mousavi, Negareh; Cheezum, Michael K.; Aghayev, Ayaz; Padera, Robert; Vita, Tomas; Steigner, Michael; Hulten, Edward; Bittencourt, Marcio Sommer; Dorbala, Sharmila; Di Carli, Marcelo F.; Kwong, Raymond Y.; Dunne, Ruth; et al.
Abstract : Background: Cardiac magnetic resonance imaging (CMR) provides useful information for characterizing cardiac masses, but there are limited data on whether CMR can accurately distinguish benign from malignant lesions. We aimed to describe the distribution and imaging characteristics of cardiac masses identified by CMR and to determine the diagnostic accuracy of CMR for distinguishing benign from malignant tumors. Methods and Results: We examined consecutive patients referred for CMR between May 2008 and August 2013 to identify those with a cardiac mass. In patients for whom there was histological correlation, 2 investigators blinded to all data analyzed the CMR images to categorize the mass as benign or malignant. For benign masses, readers were also asked to specify the most likely diagnosis. Benign masses were defined as benign neoplastic or non‐neoplastic. Malignant masses were defined as primary cardiac or metastatic. Of 8069 patients (mean age: 58±16 years; 55% female) undergoing CMR, 145 (1.8%) had a cardiac mass. In most cases (142, 98%), there was a known cardiac mass before the CMR study. Among 145 patients with a cardiac mass, 93 (64%) had a known history of malignancy. Among 53 cases that had histological correlation, 25 (47%) were benign, 26 (49%) were metastatic, and 2 (4%) were malignant primary cardiac masses. Blinded readers correctly diagnosed 89% to 94% of the cases as benign versus malignant, with a 95% agreement rate (κ=0.83). Conclusions: Although CMR can be highly effective in distinguishing benign from malignant lesions, pathology remains the gold standard in accurately determining the type of mass.